"Panoptic differential training: Bio-dynamics approach for sprint time trial cycling performance" - A critical perspective - Venkata, R. K. (Athens Journal of Sport, 2014)
Background: Intensity of the exercise mostly determines the dominant metabolic pathway for energy. In a sprint cycling 1km time trial, the dominant metabolic pathway must be ATP hydrolysis and glycolysis. Phosphocreatine (PCr) hydrolysis and Anaerobic Glycolysis lead to lactate and H+ accumulation in sarcolemmal cytosol, interfering the muscle contraction leading to fatigue and reduction of power output. To resist fatigue and to continue the high power output throughout the cycling sprint, the lactate flux is an essential phenomenon apart from the regeneration of the ATP. The appearance of H+ and lactate is simultaneous with high intensity exercise, hence the co transport of lactate-H+ is essential and the training should target both the systems to resist fatigue and sustain the cycling sprint power output at maximum throughout the time trial. Biodynamic Implications: Resting ATP and PCr stores of muscle seems less responsive to training and hence strengthening lactate transfer and oxidation appear better alternative along with more concentration on early oxidative phosphorylation. Monocarboxylate Transporter (MCT) isoforms like MCT1 and MCT4 expression should be increased to increase the lactate transport. Load of pH gradient along with lactate flux to be targeted during the training. MCTs also facilitate the H+ efflux and prevent the decrements in intracellular pH. Training Implications: High intensity training has significant influence on the status of both MCT1 and MCT4 ranging from 18% to 120%, though inter individual differences have been observed. Slow endurance training, like sub maximal sprint repetitions increases MCT1 and MCT4 expression leading to lactate uptake and oxidation. With the increase in sustaines sprints without much lactate accumulation during the initial seconds improves oxidative enzymal expression significantly. An acute high intensity sprint form of exercise could reduce the MCT1 expression considerably wherein high expression of H+ is seen in the myocyctes. . Recommendation: very high intensity sprint cycling in repetition need to be reduced to the minimum to avoid excess accumulation of H+. Instead differential training like repetitions of sub maximal runs with initial forty seconds of high intensity sprint cycling followed by sub maximal sprinting for another thirty or forty seconds. Supra maximal sprint cycling of sixty seconds to seventy seconds may be done once in a week with complete recovery in between for two to three times. The training protocol need to be structured in a more vivid form keeping in view of the bio dynamics of the sprint cycling instead of simple interval training